Answer:
no
Step-by-step explanation:
it doesnt pass the vertical line test -60 has 2 values
Answer:
look at the picture to be more clear.
Hope it helps
Answer:
f(3x) - 2g(x+1) = 12x - 5
Step-by-step explanation:
You've got f[g(x)] and g[f(x)] correct
However, f(3x) means substitute 3x for x in f(x):
f(3x) = 2(3x) - 3
⇒ f(3x) = 6x - 3
2g(x+1) = 2[4 - 3(x + 1)]
⇒ 2g(x+1) = 2[4 - 3x -3]
⇒ 2g(x+1) = 2[1 - 3x]
⇒ 2g(x+1) = 2 - 6x
f(3x) - 2g(x+1) = (6x - 3) - (2 - 6x)
⇒ f(3x) - 2g(x+1) = 12x - 5
Answer: 6 hours
Step-by-step explanation:
Given, Tim and Jim are working on a school project together.
Tim takes 10 hours to complete the school project.
If Jim worked alone, it would take him 15 hours
Let t be the time they both take if they work together.
Then, 

So, it will take<u> 6 hours</u> to complete the school project together .